Recent Advances in Aqueous Batteries with Nonmetal Cations as Charge Carriers. Issue 6 (27th January 2022) - Yu, Dongxu; Tian, Ruiyuan; Du, Fei
Abstract : During the past decades, aqueous rechargeable batteries have been receiving much attention on account of the merits of cost efficiency, high safety, and environmental benignity. Compared to metal‐ions (such as Li +, Na +, K +, Mg 2+, Zn 2+, Al 3+ etc.) as charge carriers in aqueous ion batteries, nonmetal charge carriers not only form covalent–ionic bonds in framework, but also act as reversible redox centers. Moreover, nonmetal charge carriers have advantages of low costs and high volumetric energy densities. Recently, huge efforts have been contributed to performance improvements in aqueous nonmetal cation batteries via a variety of methods. Herein, the recently reported cathode, anode materials, and newly proposed electrochemical reaction mechanisms for rechargeable aqueous nonmetal cation batteries are reviewed. Abstract : In this review, the latest advances of electrode materials for aqueous nonmetal cation batteries are summarized. Moreover, the newly proposed reaction mechanism during nonmetal cation intercalation is also introduced. It is believed that this review can raise the researchers' interests in this emerging field.